2005
DOI: 10.1002/nbm.984
|View full text |Cite
|
Sign up to set email alerts
|

MRS reveals additional hexoseN-acetyl resonances in the brain of a mouse model for Sandhoff disease

Abstract: Sandhoff disease, one of several related lysosomal storage disorders, results from the build up of N-acetyl-containing glycosphingolipids in the brain and is caused by mutations in the genes encoding the hexosaminidase beta-subunit. Affected individuals undergo progressive neurodegeneration in response to the glycosphingolipid storage. (1)H magnetic resonance spectra of perchloric acid extracts of Sandhoff mouse brain exhibited several resonances ca 2.07 ppm that were not present in the corresponding spectra f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…The presence of an extra resonance at 2.07 ppm, corresponding to N-acetylhexosamine (HexNAc), was a unique and striking feature in SD mice, detected at every time point studied, and in both cerebrum and spinal cord ( Figure 2). This finding confirms previous observations in SD patients and mice [10,11]. Moreover, the corresponding resonance increased as the disease progressed from one to four months ( Figure 2), indicating that the storage material increases with time.…”
Section: Lc-ms and Nmr Spectroscopy Show Metabolic Changes Directly Rsupporting
confidence: 92%
“…The presence of an extra resonance at 2.07 ppm, corresponding to N-acetylhexosamine (HexNAc), was a unique and striking feature in SD mice, detected at every time point studied, and in both cerebrum and spinal cord ( Figure 2). This finding confirms previous observations in SD patients and mice [10,11]. Moreover, the corresponding resonance increased as the disease progressed from one to four months ( Figure 2), indicating that the storage material increases with time.…”
Section: Lc-ms and Nmr Spectroscopy Show Metabolic Changes Directly Rsupporting
confidence: 92%
“…Recently, Lowe et al found an additional 2.07 ppm resonance in proton MRI spectra of the brain of Sandhoff mice which could be identified as originating from N-acetylhexosamine [8]. Wilken et al reported similar proton MRS findings in a child with enzymatically proven Sandhoff disease.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been reported for other metabolic alterations resulting from non‐cancer diseases. For instance, a study of intact mouse brain tissue revealed a new marker, N‐acetyl, for the lysosomal storage disorder Sandhoff disease . The detected N‐acetyl resonance was not visible in either HPLC or mass spectrometry measurements of tissue extracts, thus emphasizing the usefulness of HRMAS intact tissue studies by detecting signals that might otherwise be lost in the process of chemical extraction.…”
Section: Understanding Disease Mechanismsmentioning
confidence: 99%
“…In this section, first we discuss studies demonstrating new opportunities in diagnostic analyses, whether by providing new (lipid) biomarkers for certain diseases [25][26][27] or enabling new approaches in genetic diagnostics 28,29 and cancer subtype discrimination. 30 Further, evaluations focusing on metabolic changes due to noxae [31][32][33][34][35][36][37][38] as well as the HRMAS-assisted elucidation of molecular bacterial structures 39-41 will be reviewed.…”
Section: Understanding Disease Mechanismsmentioning
confidence: 99%